Novel Smart Textiles - Stylios, George K. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The sensing, adapting, responding, multifunctionality, low energy, small size and weight, ease of forming, and low-cost attributes of smart textiles and their multidisciplinary scope offer numerous end uses in medical, sports and fitness, military, fashion, automotive, aerospace, the built environment, and energy industries. The research and development on these new and high-value materials cross scientific boundaries, redefine material science design and engineering, and enhance quality of life and our environment. "Novel Smart Textiles" is a focused Special Issue that reports the latest research of this field and facilitates dissemination, networking, discussion, and debate.